ANALYSIS OF SPELLING ERRORS IN ENGLISH WRITING ABILITY AT THE NINTH GRADE OF SMP BP PANCASILA BENGKULU - Hanifatul Izmi; Ali Akbar Jono; Yashori Revola (STKIP Subang, 2026)
This research aims to identify and analyze the errors found and to determine the factors that cause students' errors in writing vocabulary. The subjects of this research were ninth grade students at SMP BP Pancasila Bengkulu and the basic data was taken from the results of the English test. The method used in this research is a descriptive qualitative method. The sample in this research was 20 students taken by purposive sampling. This research instrument was used to obtain data from tests and interviews, written tests in the form of vocabulary and interviews in the form of structured interviews, after which the data results were converted into documentation and assisted by observation data. The results of the research found that the total number of students' vocabulary spelling errors was 189 cases, categorized into four types, 93 cases of omission errors (4.65%), 71 cases of substitution errors (3.55%), 25 cases of insertion errors (1.25%) and no errors were found in the transposition error section or (0%). The causes of errors are due to the influence of Indonesian, lack of knowledge and hearing of various English vocabulary, difficulty re-spelling letters that have been written. This indicates that students making writing errors have their own causes according to the type of error.